Bridging population pharmacokinetic and semimechanistic absorption modeling of APX3330 - Larissa L. Silva; Robert E. Stratford; Richard Messmann; Mark R. Kelley; Sara K. Quinney (Wiley, 2024)
Abstract APX3330 ((2E)‐2‐[(4,5‐dimethoxy‐2‐methyl‐3,6‐dioxo‐1,4‐cyclohexadien‐1‐yl)methylene]‐undecanoic acid), a selective inhibitor of APE1/Ref‐1, has been investigated in treatment of hepatitis, cancer, diabetic retinopathy, and macular edema. APX3330 is administered orally as a quinone but is rapidly converted to the hydroquinone form. This study describes the pharmacokinetics of APX3330 and explores effect of food on absorption. Total plasma quinone concentrations of APX3330 were obtained following oral administration from studies in healthy Japanese male subjects (single dose‐escalation; multiple‐dose; food‐effect) and patients with cancer patients. Nonlinear mixed effects modeling was performed using Monolix to estimate pharmacokinetic parameters and assess covariate effects. To further evaluate the effect of food on absorption, a semi‐physiologic pharmacokinetic model was developed in Gastroplus to delineate effects of food on dissolution and absorption. A two‐compartment, first order absorption model with lag time best described plasma concentration‐time profiles from 49 healthy Japanese males. Weight was positively correlated with apparent clearance (CL/F) and volume. Administration with food led to an 80% higher lag time. CL/F was 41% higher in the cancer population. The semi‐physiologic model indicates a switch from dissolution‐rate control of absorption in the fasted‐state to gastric emptying rate determining absorption rate in the fed‐state. Oral clearance of APX3330 is higher in patients with cancer than healthy Japanese males, possibly due to reduced serum albumin in patients with cancer. Delayed APX3330 absorption with food may be related to higher conversion to the more soluble but less permeable hydroquinone form in the gastrointestinal tract. Future work should address pharmacokinetic differences between APX3330 quinone and hydroquinone forms.